Towards a Digital Lexicon of Jewish Revisions of the Septuagint (Greek/Hebrew-English/German): First Steps and Considerations for Analysing the Vocabulary of Symmachus - Albrecht, Felix (Journal of septuagint and cognate studies, 2024)
This article emerges from the ongoing development of an Editio critica maior of the Greek Psalter and the preparatory work for the creation of its Hexaplaric apparatus. This effort includes the systematic recording and grammatical annotation of Hexaplaric readings found in Psalter manuscripts and Patristic quotations. Concurrently, a 'Digital Index of Jewish Revisions of the Septuagint' is planned, which will encompass Hebrew equivalents, references, and detailed grammatical analyses. This initiative is based on the Göttingen Hexapla Database, which currently contains over 136,000 entries, primarily attributed to Symmachus. Given Symmachus’ significant contributions, the analysis begins with his Psalter vocabulary, comprising 224 hapax legomena, 18 of which are unique within Greek literature. The article presents two specific examples that demonstrate the limitations of current Septuagint lexica, specifically in their treatment of Jewish recensions — a deficiency previously highlighted by Johan Lust. Despite some initial progress on a Symmachus lexicon, a comprehensive lexicon of Jewish recensions remains a crucial research need. The Göttingen project aims to address this challenge by first developing a 'Digital Index' and subsequently a 'Digital Lexicon of Jewish Revisions of the Septuagint'.